JUDGMENT FREEDOM MODEL IN JUDGING CORRUPTION CRIMINAL CASES - Maman Budiman (International Journal of Latin Notary, 2021)
The independence of judges is based on independence, therefore it is guaranteed in law. Judges adjudicating corruption cases must be professional, clean, honest, courageous and free from intra-judicial and extra-judicial influences. The problem in this research is how the model of freedom of judges in judging cases of corrup-tion in the Corruption Court, especially in the Corruption Court at the Kls I A District Court in Bandung. This research was carried out with a normative and empirical juridical approach, namely studying legal materials systematically to discuss problems obtained from literature studies, by analyzing a legal problem through the concept of legal philosophy associated with the freedom of Judgment in adjudicating corruption cases and The data obtained were ob-tained from field research and interviews. The purpose of this research is to examine the model of Judgment freedom in examining, adjudicating and deciding cases of Corruption Crime, while the benefits of this research are expected to produce scientific work that is beneficial for the development of legal science as well as material for scientific work that will be published in the National Journal., as well as teaching material for students of the Faculty of Law in particular who take courses in Criminal Law, Criminal Procedure Law and Legal Philosophy. From this research, it is found that judges in deciding cases of corruption can apply existential freedom and social freedom to produce a just decision based on the one and only Godhead.